2013
DOI: 10.1093/intimm/dxt033
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke impairs phagocytosis of apoptotic neutrophils by alveolar macrophages via inhibition of the histone deacetylase/Rac/CD9 pathways

Abstract: Efferocytosis, which is the homeostatic phagocytosis of apoptotic cells, prevents the release of toxic intracellular contents and subsequent tissue damage. Impairment of efferocytosis was reported in alveolar macrophages (AMs) of patients with chronic obstructive pulmonary disease (COPD), a common disease caused by smoking. In COPD, histone deacetylase (HDAC) activity is reduced in AMs. We investigated whether the reduction of HDAC activity is associated with the impairment of efferocytosis. Murine AMs were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 28 publications
1
28
1
1
Order By: Relevance
“…CD9, a transmembrane protein of the tetraspanin family, facilitates some pathogens and other foreign matters. HDAC and Rac have already been demonstrated that they are required for efferocytosis [100]. Noda et al reported that smoking could impair efferocytosis of neutrophils via inhibition of HDAC/Rac/CD9 pathways (Figure 2, c4).…”
Section: Neutrophils In Copdmentioning
confidence: 92%
See 2 more Smart Citations
“…CD9, a transmembrane protein of the tetraspanin family, facilitates some pathogens and other foreign matters. HDAC and Rac have already been demonstrated that they are required for efferocytosis [100]. Noda et al reported that smoking could impair efferocytosis of neutrophils via inhibition of HDAC/Rac/CD9 pathways (Figure 2, c4).…”
Section: Neutrophils In Copdmentioning
confidence: 92%
“…Neutrophils contain a great deal of proteases, inflammatory mediators, and oxidants [100]. IL-22/IL-22R signaling pathway plays a pivotal role in antimicrobial defense.…”
Section: Neutrophils In Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Statins cause the enzymes Rac and RhoA to sequester derived from the model, as is the BMI-dependent slope of 0.6. From these lines, it can be seen that without statins the differences between smoking status are large, but with statins the differences are smaller.…”
Section: Discussionmentioning
confidence: 98%
“…7 Statins cause the enzymes Rac and RhoA to sequester Figure 1 Bronchoscopy flow chart. Approximately half of the subjects assessed were deemed ineligible for research bronchoscopy-the majority of those being excluded on safety grounds due to comorbidity.…”
Section: Discussionmentioning
confidence: 99%